Political Theology - Moltmann, Jürgen 1926-2024 (1971)
“Political theology is therefore not simply political ethics but reaches further by asking about the political consciousness of theology itself. It does not want to make political questions the central theme of theology or to give political systems and movements religious support. Rather, political theology designates the field, the milieu, the environment, and the medium in which Christian theology should be articulated today.”